Computation of FRAP recovery times for linker histone: chromatin binding on the basis of Brownian dynamics simulations - Öztürk, Mehmet Ali; Wade, Rebecca C. (Biochimica et biophysica acta. General subjects, 2020)
Background Fluorescence recovery after photobleaching (FRAP) studies can provide kinetic information about proteins in cells. Single point mutations can significantly affect the binding kinetics of proteins and result in variations in the recovery half time (t50) measured in FRAP experiments. FRAP measurements of linker histone (LH) proteins in the cell nucleus have previously been reported by Brown et al. (2006) and Lele et al. (2006). Methods We performed Brownian dynamics (BD) simulations of the diffusional association of the wild-type and 38 single or double point mutants of the globular domain of mouse linker histone H1.0 (gH1.0) to a nucleosome. From these simulations, we calculated the bimolecular association rate constant (kon), the Gibbs binding free energy (ΔG) and the dissociation rate constant (koff) related to formation of a diffusional encounter complex between the nucleosome and the gH1.0. Results We used these parameters, after application of a correction factor to account for the effects of the crowded environment of the nucleus, to compute FRAP recovery times and curves that are in good agreement with previously published, experimentally measured FRAP recovery time courses. Conclusions Our computational analysis suggests that BD simulations can be used to predict the relative effects of single point mutations on FRAP recovery times related to protein binding. General Significance BD simulations assist in providing a detailed molecular level interpretation of FRAP data.
Gesehen am 20.10.2020